STRENGTHENING SELF-CONFIDENCE CHARACTER IN 5-6 YEAR-OLD CHILDREN THROUGH REINFORCEMENT ACTIVITIES OF ACHIEVEMENT BOARDS AT RA AL HIDAYAH - Indah Qomariyah; Riris Wahyuningsih; Fitriatul Masruroh (International Conference on Humanity Education and Society (ICHES), 2023)
School is an educational institution to build students character, one of which is self-confidence. In fact, many children lack self-confidence in rural areas. RA Al Hidayah is an RA who implements achievement board reinforcement activities to strengthen self-confidence. This study aims to determine the application and effectiveness of achievement board reinforcement activities. The research method used is qualitative with the type of phenomenology. This research was conducted at RA Al Hidayah with the research subjects being the principal, class teachers and group B children. Data collection techniques were carried out by researchers namely observation, interviews and documentation. The results of the research conducted show that there are still children who lack confidence when carrying out activities or activities carried out when the learning process takes place inside or outside the classroom, children lack confidence when they come forward or do learning while playing. From the results of the final accumulation in group B, 12 children were assessed using 3 indicators, namely the results obtained were 4 children developing very well and 8 children developing as expected. This shows that achievement board reinforcement activities are very suitable for increasing the character of self-confidence in children.